State of the dispersant and particle surface during wet-jet milling for preparation of a stable slurry - Hotta, Yuji; Yılmaz, Hüseyin; Shirai, Takashi; Ohota, Kazutoku; Sato, Kimiyasu; Watari, Koji (Blackwell Publishing, 2008)
Wet-jet-milled alumina slurries exhibited distinctly different stability behavior compared with ball-milled ones in terms of reflocculent efficiency and rheological properties. The distinction was attributed to the different behavior of the same dispersant (NH4+ salt of poly(acrylic acid); PAA-NH4+) in ball milling and wet-jet milling. Alumina particles after the wet-jet milling retained the initial surface conditions, although ball-milled alumina particles yielded more hydroxyl groups on the surface. Furthermore, degradation of dispersant on milling was investigated qualitatively. Infra-red analysis and isoelectric point measurements suggested that degradation of the dispersant occurred during ball milling, indicating neutralization of the dispersant due to formation of monodentate COOX groups. On the other hand, in the case of wet-jet milling, COO- groups of PAA-NH4+ were not degraded at all, indicating maintenance of the structures of dispersant with electrostatic repulsion. Change in the polymer size of the dispersant by different milling methods was confirmed using high performance liquid chromatography (HPLC) measurements. The HPLC results of the wet-jet milled samples showed that a dispersant with a larger molecular size was generated. Force measurement on approach via the colloid probe method in the centrifuged supernatant of the milled slurries confirmed that the interaction distance between an alpha-alumina colloid probe and c-sapphire surface was about two times larger in the wet-jet-milled slurry supernatant compared with the ball milled one. Thus, it was found that wet-jet milling process led to a stable slurry because of the maintenance of not only steric repulsion but also electrostatic repulsion.
Keywords: Al2o3 Slurries; Rheological Properties; Alumina Slurries; Slip; Suspensions; Adsorption; Optimization; Filtration; Behavior